Redescription of the little known hermit crab, Clibanarius clibanarius (Herbst, 1791) (Decapoda: Anomura: Diogenidae), based on material from southern India and type material - Komai, Tomoyuki; Reshmi, Rema; Rahayu, Dwi Listyo; Kumar, Appukuttannair Biju (Zootaxa, 2019)
A little known littoral hermit crab, Clibanarius clibanarius (Herbst, 1791), is redescribed on the basis of material from southern India, supplemented by the photographs of the type material. The species appears closest to C. infraspinatus Hilgendorf, 1869, but the absence of a prominent ventral spine or protuberance on the cheliped meri immediately distinguishes C. clibanarius from C. infraspinatus. Although the species has been reported from wide areas in the Indo-West Pacific, records outside of India still needs to be verified.